Relationship of soil physico chemical properties with elevation and geographical directions. Issue 1 (June 2021) - Imran; Amanullah; Naveed, S; Khan, I; Sajid, M; Mahmood, T; Hussain, I; Ilyas, M; Ali, I; Ullah, S; Kamal, A; Altawaha, A R; et al.
Abstract: The core findings of this study revealed that physicochemical properties fluctuate with soil texture and soil class. Sandy soil showed inconsistent variation with geographical directions. Bulk density, lime content, EC and pH decreases with topography and soil elevation while these parameters increased from surface to subsurface soil within a profile. Nitrogen, phosphorus, potassium and micronutrient increased with increase in elevation. All these parameters decreased from surface to subsurface soil. Water holding capacity and saturation percentage increased with increase in elevation, while decreased from surface to subsurface soil. Based on the critical level of phosphorus, the altitude was low in available P and available P was quite low than the crop requirements and so they will be classified as phosphorus-deficient soils.